Reciprocal associations between early maladaptive schemas and depression in adolescence: long-term effects of childhood abuse and neglect - Yumeng Wang; Yemiao Gao; Jinmeng Liu; Rong Bai; Xia Liu (BMC, 2023)
Abstract Background Adolescent depression has grown to be a major social concern in China. During the coronavirus pandemic, the incidence of depression among Chinese adolescents increased substantially. More research is required to inform the prevention and intervention of adolescent depression in China. Depression is associated with Early Maladaptive Schemas (EMSs). Childhood abuse and neglect are distal antecedents of adolescent depression. It is not known how depression and EMSs interact in adolescence and how childhood abuse and neglect contribute to this relationship. This study aimed to examine the reciprocal relationships between depression and EMSs, as well as the long-term effects of childhood abuse and neglect on depression and EMSs during adolescence. The work also investigates gender differences in these mechanisms. Methods Using a two-wave longitudinal design, we recruited 3,485 Chinese adolescents (M age = 13.2; 43.2% females) from three Shanxi Province, China middle schools. All participants completed self-report questionnaires addressing childhood abuse and neglect, depression, and EMSs. Structural equation models examined reciprocal relationships between depression and EMS, as well as the effect of childhood abuse and neglect on depression and EMSs. Multi-group analysis addressed gender differences. Results Results indicated that greater depression predicted more EMSs measured later, but EMSs did not predict subsequent depression. Childhood abuse and neglect had different effects on depression and EMSs during adolescence. Specifically, exposure to childhood abuse related to more severe depression and EMSs in adolescence and contributed to the perpetuation of EMSs by increasing depression. Exposure to childhood neglect showed a direct effect on depression and indirectly reinforced subsequent EMSs through depression. There were no gender differences. Conclusion These findings contribute to a better understanding of the emergence and course of depression in early adolescence, suggesting that childhood abuse and neglect are critical early risk factors. Additionally, depression plays a key role in promoting schema perpetuation among adolescents exposed to childhood maltreatment, providing important implications for relevant prevention and intervention in early adolescence.